Phonon transports in single-walled carbon nanotube films with different structures determined by tensile tests and thermal conductivity measurements - Hisatoshi Yamamoto; Yutaro Okano; Keisuke Uchida; Makoto Kageshima; Toru Kuzumaki; Shugo Miyake; Masayuki Takashiri (Carbon Trends)
The phonon transport properties of single-walled carbon nanotubes (SWCNTs) undergo significant changes when shaped into individuals, bundles, or films. Among these, SWCNT films are the most useful for industrial applications; however, their phonon transport properties have not been thoroughly investigated. This study estimated the phonon transport properties—specifically, the sound velocity, lattice thermal conductivity, and phonon mean free path (MFP)—of SWCNT films by conducting tensile tests and thermal conductivity measurements. The SWCNT films were prepared through vacuum filtering, with their structures modified by adjusting the ultrasonic dispersion amplitude during SWCNT ink production. The average sound velocity of the SWCNT films reached a maximum of 692 m/s at the lowest dispersion amplitude of 30 % (nominal value of 200 W), decreasing as the dispersion amplitude increased. The maximum values of lattice thermal conductivity and phonon MFP were 50.9 W/(m⋅K) and 119 nm, respectively, observed at dispersion amplitudes of 50 % and 90 %. These results arise from the complex interaction of factors such as defect density, mass density, SWCNT bundle diameter, and SWCNT length. This analytical method provides a straightforward approach to determine the detailed phonon transport properties of CNT films.